The ex situ exsolved exsolved Ni-Ru alloy from nickel-ruthenium co-doped SrFeO perovskite as a potential catalyst for C=C and C=O hydrogenation - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (SUSTAINABLE ENERGY & FUELS, 2024)
Keywords: LIQUID-PHASE HYDROGENATION; OXIDE FUEL-CELLS

Catalytic hydrogenation of cinnamaldehyde over nanocrystalline nickel-doped lanthanum aluminate: synergistic effect of nickel and oxygen vacancies - Bhavisha, Meloth; Balamurugan, Sarkarainadar; Venkatesha, Naragalu J.; Gopinath, Chinnakonda S.; Sakthivel, Ayyamperumal (ChemCatChem, 2025)
Nickel-doped lanthanum aluminium perovskite, LaAl1-xNixO3-delta with x = 0, 0.1, 0.2, 0.3, 0.4,0.5, 0.6, and 0.75 (LANx), were obtained through a combustion method followed by a calcination process. The obtained LANx materials crystallized in the cubic structure by the Pm-3m (221) space group. The nanocrystalline nature of the LANx materials was confirmed by the average crystalline size determined using Debye-Scherrer formula. X-ray photoelectron spectroscopy (XPS) studies showed that nickel was present in the +2 and +3 oxidation states. The introduction of nickel resulted in distinct peaks in TPR in the temperature range of 200-600 degrees C, with an enhanced reducibility of the materials. The LANx materials were thoroughly assessed for their effectiveness in the hydrogenation of cinnamaldehyde. The maximum catalytic activity (cinnamaldehyde conversion of 98% with a hydrocinnamylalcohol selectivity 96.5%) was observed with the presence of the LAN7 catalyst at 150 degrees C for 6 h at a H2 pressure of 10 bar. The catalytic activity is maintained even after four cycles, which broadens the application scope as the material is sustainable, scalable, cost-effective, and a potential alternative to reported noble metal catalysts. The synergistic effect of nickel and oxygen vacancies in the catalyst improves the reducibility and provides a promising catalytic activity in the cinnamaldehyde hydrogenation.
Keywords: Cinnamaldehyde; Hydrocinnamylalcohol; Hydrogenation; Nickel; Perovskite oxide

Enhanced structural stability and selective furfural hydrogenation over Ru and Si co-doped SrFeO3-δ perovskites - Bhavisha, Meloth; Joseph, Arsha P.; Gopinath, Chinnakonda S.; Balamurugan, Sarkarainadar; Venkatesha, Naragalu J.; Ganesh, Venkatachalam; Sakthivel, Ayyamperumal (New Journal of Chemistry, 2026)
Doping of SrFeO3-delta with transition and non-transition elements provides a powerful route to modulate its physicochemical properties. In this investigation, a series of ruthenium and silicon co-doped SrFeO3-delta (SrFe0.95-xRu0.05SixO3-delta) samples were prepared via the sol-gel combustion method using hexamine as fuel. The doped samples crystallized in the cubic structure with the Pm3m (221) space group. The presence of Si4+, Fe3+, Fe4+ and Ru4+ in the SrFe0.95-xRu0.05SixO3-delta sample was confirmed by XPS analysis. The presence of an EPR signal at g = 1.9393 and the temperature-programmed desorption of oxygen (TPD-O2) analyses validated the presence of oxygen vacancies. The ruthenium and silicon co-doped SrFeO3-delta effectively hydrogenates biomass-derived platform molecule furfural with 95% conversion and exhibits 88% furfuryl alcohol selectivity at 185 degrees C for 6 h under 30 bar H2 pressure. The spent ruthenium-doped SrFeO3-delta (SrFe0.95Ru0.05O3-delta) catalyst exhibited a phase transformation from the cubic perovskite structure to the brownmillerite phase with the exsolution of the metallic ruthenium species. The exsolution of metallic ruthenium can be correlated with the formation of secondary products, viz., non-selective hydrogenation leads to tetrahydrofurfuryl alcohol, furan, and methylfuran. Ruthenium and silicon co-doped perovskite oxide showed selectivity towards furfuryl alcohol with the retention of its original cubic perovskite structure. This modification of perovskite oxide with ruthenium and silicon demonstrates a highly effective strategy for engineering stable and chemo-selective catalysts for the sustainable upgrading of platform chemicals.